Penguatan Nilai Karakter Gotong Royong melalui Keluarga dalam Perspektif Pendidikan Karakter - Pradita Ujiyanto; Maria Helena Sri Rahayu (Academy of Education Journal, 2026)
This study aims to determine how to strengthen the value of mutual cooperation through the family in the perspective of character education. The results of the study indicate that the family has a very strategic role in strengthening the value of mutual cooperation character in children. Strategies that can be carried out by families to strengthen the value of mutual cooperation character in children include: teaching the values of mutual cooperation, making collaborative rules, developing understanding and awareness, and carrying out mutual cooperation activities together. This study also shows that strengthening the value of mutual cooperation character through the family can form a strong and good character in children.